Transitions in Arctic ecosystems: Ecological implications of a changing hydrological regime. Issue 3 (30th March 2016) - Wrona, Frederick J.; Johansson, Margareta; Culp, Joseph M.; Jenkins, Alan; Mård, Johanna; Myers‐Smith, Isla H.; Prowse, Terry D.; Vincent, Warwick F.; Wookey, Philip A.
Abstract: Numerous international scientific assessments and related articles have, during the last decade, described the observed and potential impacts of climate change as well as other related environmental stressors on Arctic ecosystems. There is increasing recognition that observed and projected changes in freshwater sources, fluxes, and storage will have profound implications for the physical, biogeochemical, biological, and ecological processes and properties of Arctic terrestrial and freshwater ecosystems. However, a significant level of uncertainty remains in relation to forecasting the impacts of an intensified hydrological regime and related cryospheric change on ecosystem structure and function. As the terrestrial and freshwater ecology component of the Arctic Freshwater Synthesis, we review these uncertainties and recommend enhanced coordinated circumpolar research and monitoring efforts to improve quantification and prediction of how an altered hydrological regime influences local, regional, and circumpolar‐level responses in terrestrial and freshwater systems. Specifically, we evaluate (i) changes in ecosystem productivity; (ii) alterations in ecosystem‐level biogeochemical cycling and chemical transport; (iii) altered landscapes, successional trajectories, and creation of new habitats; (iv) altered seasonality and phenological mismatches; and (v) gains or losses of species and associated trophic interactions. We emphasize the need for developing a process‐based understanding of interecosystem interactions, along with improved predictive models. We recommend enhanced use of the catchment scale as an integrated unit of study, thereby more explicitly considering the physical, chemical, and ecological processes and fluxes across a full freshwater continuum in a geographic region and spatial range of hydroecological units (e.g., stream‐pond‐lake‐river‐near shore marine environments). Key Points: Changes in the Arctic freshwater sources, fluxes and storage have profound implications for ecosystems Significant uncertainty remains in forecasting impacts on ecosystem properties and processes Enhanced circumpolar catchment‐scale research efforts are needed to reduce uncertainties